STRATEGI PENGEMBANGAN PARIWISATA KARIMUNJAWA OLEH DINAS PARIWISATA DAN KEBUDAYAAAN KABUPATEN JEPARA DALAM RANGKA MENINGKATKAN ARUS KUNJUNGAN WISATAWAN - Teguh Arief Priyanta; Puji Astuti; Lusia Astrika (Journal of Politic and Government Studies, 2013)
Jepara district that has a complete tourism potential when compared to other regions. One of the tourist attraction in Jepara is Karimunjawa. This study aims to determine what strategies adopted by the Government in developing the tourism Karimunjawa. And barriers faced by the tourism development efforts. Many reasons why tourism a top priority in terms of development. That is because the tourism industry is related to cross-cutting activities. In addition to generating revenue for the area of goods and services, tourism development is also to create new jobs, boosting labor absorbing growth products. Based on all the tourism potential that can be found in the Marine National Park Karimunjawa, then for utilization can not be done by way of a modest, meaning that the potential is still in need of a tour package.Keywords: Publications, tourists, strategies, governments, development.